Quantitative modeling of the relationship between Basel III Capital Buffers and key strategic solutions: A case study of commercial banks in Vietnam - Nguyen, Khuong; Vu, Mai Chi; Nguyen, Thu Huong (Edelweiss Applied Science and Technology, 2025)
The Basel III Capital Buffers were introduced by the Basel Committee on Banking Supervision after the 2008 global financial crisis to strengthen global bank stability by providing additional capital layers that can absorb potential losses and manage excessive credit growth. In Vietnam, the implementation of these buffers has presented considerable challenges, especially for commercial banks, where tailored solutions must be customized to align with the unique scale, structure, and characteristics of each institution. This article examines the impact of various strategic approaches on implementing Basel III Capital Buffers in Vietnamese commercial banks. The regression research model employs a 5-level Likert scale, using a questionnaire of 6 variables representing 40 distinct indicators, in a survey conducted across 115 banking institutions in Vietnam. The findings reveal that strategies for capital increases through securities issuance, reinvestment from business activities, and system upgrades significantly influence buffer implementation. Securities-related capital increases have the most significant effect, followed by system upgrades and business reinvestment. In contrast, delays in state capital injections and persistent operational challenges hinder progress. The study offers practical recommendations to enhance Basel III compliance in Vietnam by optimizing capital management strategies and addressing key implementation barriers to ensure the long-term resilience of the banking sector.